2013
DOI: 10.1530/jme-13-0064
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes: new targets of melanocortin 4 receptor actions

Abstract: Astrocytes exert a wide variety of functions with paramount importance in brain physiology. After injury or infection, astrocytes become reactive and they respond by producing a variety of inflammatory mediators that help maintain brain homeostasis. Loss of astrocyte functions as well as their excessive activation can contribute to disease processes; thus, it is important to modulate reactive astrocyte response. Melanocortins are peptides with well-recognized anti-inflammatory and neuroprotective activity. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 212 publications
(179 reference statements)
2
26
0
1
Order By: Relevance
“…We previously found that PVM/Ms are activated in animals exposed to loud sound or induced to inflammation(Zhang et al 2013b; Zhang et al 2013a). Similar astrocyte activation is seen in brain ischemic diseases(Caruso et al 2013). Is PVM/M “activation” also elicited by hypoxia?…”
Section: Discussionsupporting
confidence: 52%
“…We previously found that PVM/Ms are activated in animals exposed to loud sound or induced to inflammation(Zhang et al 2013b; Zhang et al 2013a). Similar astrocyte activation is seen in brain ischemic diseases(Caruso et al 2013). Is PVM/M “activation” also elicited by hypoxia?…”
Section: Discussionsupporting
confidence: 52%
“…Glucose is transported from the blood through endothelium cells by astrocytes (Simpson et al, 2007), which actively modulate neuronal homeostasis and metabolism in the central nervous system (Caruso et al, 2013). Astrocytes extend processes terminating in end feet that encapsulate capillaries to control the blood-brain barrier and molecular exchange between the blood and brain parenchyma (Abbott et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is thought to explain 2-6% of extremely obese childhood and adolescent cases (Farooqi et al, 2003;Hinney et al, 2003Hinney et al, , 2006Santini et al, 2004;Wang & Tao, 2011). The MC4R is a membrane-bound G-protein-coupled receptor that activates adenylate cyclase; in response to the α-melanocyte-stimulating hormone (α-MSH), MC4R induces production of cAMP (Stutzmann et al, 2008;Caruso et al, 2013). The expression of MC4R is restricted to the brain, where it is found in hypothalamic nuclei involved in food intake regulation (Mountjoy et al, 1994).…”
Section: Introductionmentioning
confidence: 99%